Big stories and small stories in the psychological relief work after the earthquake disaster : life and death (2015)
As the strict setting of psychoanalysis typically shows, psychotherapy has been based on the free will and decision of patients to visit psychotherapists and pay the fee for sessions. However, recently more and more psychotherapists have been engaged with work in hospitals (HIV counseling, terminal care, genetic counseling etc.), schools and even in places hit by natural disaster and social crisis. Psychotherapy is used for crisis intervention. In such cases people can get psychological help as a service offered on site, sometimes without paying a fee. Although the conventional model of psychotherapy is still widely used, this new type of psychotherapy may bring about a fundamental change in the idea of psychotherapy.